2010
DOI: 10.1002/jhm.589
|View full text |Cite
|
Sign up to set email alerts
|

Impact and recognition of cognitive impairment among hospitalized elders

Abstract: BACKGROUND:Older adults are predisposed to developing cognitive deficits. This increases their vulnerability for adverse health outcomes when hospitalized.OBJECTIVE:To determine the prevalence and impact of cognitive impairment (CI) among hospitalized elders based on recognition by lCD‐coding versus screening done on admission.DESIGN:Observational cohort study.SETTING:Urban public hospital in Indianapolis.PATIENTS:997 patients age 65 and older admitted to medical services between July 2006 and March 2008.MEASU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
120
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 60 publications
6
120
2
1
Order By: Relevance
“…3,4,6,[9][10][11] Furthermore, increased complexity of the discharge instructions due to a greater burden of comorbid illnesses and higher prevalence of cognitive impairment among older adults may result in an elevated risk of non-comprehension. 1,2,[12][13][14] In this study, we determined the prevalence of noncomprehension of the discharge instructions and identified patient characteristics associated with non-comprehension among older adults discharged from the medical and surgical units of a large urban hospital. As a secondary analysis, we assessed the prevalence of non-compliance with the discharge instructions and analyzed factors associated with noncompliance among study participants who understood their discharge instructions.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,6,[9][10][11] Furthermore, increased complexity of the discharge instructions due to a greater burden of comorbid illnesses and higher prevalence of cognitive impairment among older adults may result in an elevated risk of non-comprehension. 1,2,[12][13][14] In this study, we determined the prevalence of noncomprehension of the discharge instructions and identified patient characteristics associated with non-comprehension among older adults discharged from the medical and surgical units of a large urban hospital. As a secondary analysis, we assessed the prevalence of non-compliance with the discharge instructions and analyzed factors associated with noncompliance among study participants who understood their discharge instructions.…”
Section: Introductionmentioning
confidence: 99%
“…Two geriatric syndromes in particular, delirium and falls, are associated with increased length of stay, increased healthcare costs, and substantial morbidity. 9,10 Multifactorial interventions such as the Hospital Elder Life Project (HELP) have been shown to prevent delirium and falls. [11][12][13][14] Studies of the HELP intervention demonstrated benefits on outcomes that are important to hospitalists, including shortened length of stay.…”
Section: Many Health Conditions In Older Patients Are Multifactorialmentioning
confidence: 99%
“…5 Patients may not receive the ideal level of care even if the presence of CI is established, and very disturbingly, as many as 60% 5 of patients with CI will not have the diagnosis noted on their chart.…”
Section: Introductionmentioning
confidence: 99%